Detecting eve in communication with continuous-variable Einstein-Podolsky-Rosen correlations - Messikh, Azeddin (2007)
We study the validity of the entanglement parameter introduced in a recent publication by Guangqiang et al. Phys. Rev. A 73 012314 (2006)] for detecting Eve, the eavesdropper. We have found that Eve can be detected using this parameter only if Alice establishes a quantum correlation between the Einstein-Podolsky-Rosen (EPR) pair. This quantum correlation is related to the possibility of an apparent violation of the Heisenberg inequality for the quadrature components of the EPR pair.